INOVASI APLIKASI SADAR LINGKUNGAN BERBASIS ANDROID (SALING BANGGA) - Suwali, Suwali; Suprapto, Suprapto; Panunggul, Victor Bintang; Sitanini, Ayu; Noviani, Faizah; Irma Azalia, Inez (Awatara Publisher, 2024)
Climate change and environmental degradation are pressing global issues, particularly in Indonesia. Many communities lack the information and facilities to engage in environmental conservation efforts. The